Satellite glial cell P2Y(12 )receptor in the trigeminal ganglion is involved in lingual neuropathic pain mechanisms in rats - Katagiri, Ayano (BioMed Central, 2012)
BACKGROUND: It has been reported that the P2Y(12 )receptor (P2Y(12)R) is involved in satellite glial cells (SGCs) activation, indicating that P2Y(12)R expressed in SGCs may play functional roles in orofacial neuropathic pain mechanisms. However, the involvement of P2Y(12)R in orofacial neuropathic pain mechanisms is still unknown. We therefore studied the reflex to noxious mechanical or heat stimulation of the tongue, P2Y(12)R and glial fibrillary acidic protein (GFAP) immunohistochemistries in the trigeminal ganglion (TG) in a rat model of unilateral lingual nerve crush (LNC) to evaluate role of P2Y(12)R in SGC in lingual neuropathic pain. RESULTS: The head-withdrawal reflex thresholds to mechanical and heat stimulation of the lateral tongue were significantly decreased in LNC-rats compared to sham-rats. These nocifensive effects were apparent on day 1 after LNC and lasted for 17 days. On days 3, 9, 15 and 21 after LNC, the mean relative number of TG neurons encircled with GFAP-immunoreactive (IR) cells significantly increased in the ophthalmic, maxillary and mandibular branch regions of TG. On day 3 after LNC, P2Y(12)R expression occurred in GFAP-IR cells but not neuronal nuclei (NeuN)-IR cells (i.e. neurons) in TG. After 3 days of successive administration of the P2Y(12)R antagonist MRS2395 into TG in LNC-rats, the mean relative number of TG neurons encircled with GFAP-IR cells was significantly decreased coincident with a significant reversal of the lowered head-withdrawal reflex thresholds to mechanical and heat stimulation of the tongue compared to vehicle-injected rats. Furthermore, after 3 days of successive administration of the P2YR agonist 2-MeSADP into the TG in naïve rats, the mean relative number of TG neurons encircled with GFAP-IR cells was significantly increased and head-withdrawal reflex thresholds to mechanical and heat stimulation of the tongue were significantly decreased in a dose-dependent manner compared to vehicle-injected rats. CONCLUSIONS: The present findings provide the first evidence that the activation of P2Y(12)R in SGCs of TG following lingual nerve injury is involved in the enhancement of TG neuron activity and nocifensive reflex behavior, resulting in neuropathic pain in the tongue.